A KPI model for logistics partners' search and suggestion to create virtual organisations. (1st January 2013) - Correia Alves, Omir; Rabelo, Ricardo J.
This paper presents an exploratory and qualitative work of a novel model for the selection of the most adequate logistics providers to compose virtual organisations. It includes a performance measurement model and a supporting methodology that considers the intrinsic dynamics, autonomy and temporality of virtual organisations, involving both intra and inter-organisational strategic indicators. The model is flexible in terms of both allowing performance indicator weight relaxation and being adapted according to the organisation's governance model. A software prototype was developed and interviews with specialists were carried out to evaluate the model. Results are discussed at the end.